The Influence of AI-Driven Learning Media on Football Motivation and Passing Ability - Destya, Muhammad Reza (UNIB Press, 2026)
This study aims to test the effectiveness of artificial intelligence (AI)-based learning media in improving students' soccer passing skills and learning motivation compared to conventional learning. The study used a quasi-experimental design with a pretest–posttest control group pattern on 60 FIK UNIMED students who were divided into experimental and control groups. The experimental group received AI-based learning with real-time feedback, personalized training, and gamification elements, while the control group used conventional methods. The research instruments included a passing skills test and a learning motivation scale. Data analysis used ANCOVA/t-test and Pearson correlation. The results showed that the experimental group had a significant increase in passing skills and learning motivation compared to the control group (p < 0.01) with a medium–large effect size. There was a positive relationship between increased motivation and improved passing skills. AI-based learning media effectively improved psychomotor and affective learning outcomes as well as skill retention.